Prototype of molecular biology courseware for inclusive education system: An instructional interface - Tosho, Abdulrauf; Abdul Mutalib, Ariffin; Ab Salam, Sobihatun Nur (Universiti Teknologi MARA (Terengganu), 2016)
This paper provides a research approach in developing an e-learning environment for inclusive learners.By capturing and modelling the multimedia 3-D knowledge into an instructional interface for teaching and assessing Molecular Biology Courseware for student in inclusive learning environment.The research proposed and developed a Conceptual Design Model for Courseware for Inclusive Education System, called C4IES. The experimental result conducted from the subject experts using the proposed prototype has demonstrated a great potential. Where, out of 10 experts 90% agreed that the proposed Multimedia environment has demonstrated a high usability in enhancing molecular concept (DNA) and practical skills of student in self learning practicing the laboratory task while away from on-campus environment. This could also be as guidance for the developer or anyone who intent to develop courseware for inclusive environment.